Lexis in Demography - Hulíková Tesárková, Klára (SpringerBriefs in Population Studies,, 2018)
This book explores the life of economist and social scientist Wilhelm Lexis and the key demographic instrument named after him: the Lexis diagram. It describes this vital tool, which helps demographers visualize data, and examines its various forms through a specially designed example. As a result, readers get to see the Lexis diagram in practice and gain first-hand insight into its different forms. The authors first present a brief description of the life of W. Lexis with information about his childhood, studies, and work. Coverage details the places closely related to him as well as his working positions. It also lists and characterizes his publications. The book then goes on to summarize and describe the chronological development of the Lexis diagram, from initial developments through the specific contributions of W. Lexis to the refinements of those who followed. Throughout, it clearly describes as well as graphically and prac tically illustrates all the different versions of the diagram covered. Next, readers are presented with contemporary practical applications, including: Statistical Analysis System (SAS), R, and Lexis software as well as selected key-studies from demographic, epidemiologic, and migration research. The Lexis diagram is an essential tool for working correctly with demographic data. This book commemorates the man who helped to develop these diagrams and his unquestionable influence on demography. It also provides readers with deep knowledge and insights into this basic, yet important, tool.